(3CNdGbjGJ GdYed (B/s - (3GdScGQfI, HdGd Ndas ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2011)
(3eaghe CNdGbjGJ GdYed , GNdGbjGJ GdYed GdhXjaj , bje GdaQO h GdefXeGJ h CNdGbjGJ GdYed , GdGfVHGW h GdGdJRGe GdhXjaj , GdeSDhdjI GdGLJeGYjI defXeGJ GdCYeGd , eOhfI h bhGYO GdSdhc , GdSdhc GdYOhGfj ddehXa h CNdGbjGJ GdYed , GdaSGO GdGOGQj , GdMhceI , GdKbGaI GdJfXjejI h CNdGbjGJ GdYed , GdGfJQfjJ h CNdGbjGJ GdYed , CNdGbjGJ GdYed h egGQGJ GdGJUGd eY GdCNQjfs
Keywords: (3CNdGbjGJ GdegfIs; (3EOGQI GdCYeGds; (3GdYeds